Numerical Studies Using Full Car Model for Combined Primary and Cabin Suspension. (2016) - Sharma, S.K.; Pare, Vinod; Chouksey, Manoj; Rawal, B.R.
Abstract: Primary suspension system isolates vehicle's chassis from road irregularities, while cabin suspension system isolates cabin from chassis vibrations. Suspension system design requires high standard of "ride comfort" and "vehicle handling" simultaneously. However, both of these requirements of the ride comfort and vehicle handling are conflicting. Various types of car models have been used in literature to simulate suspension systems, e.g. quarter car model, half car model and full car model. This paper attempts development of 10 degree of freedom Full Car model with integration of primary and cabin suspension in the Simulink environment to see the effect of cabin suspension on the ride comfort over the primary suspension system. The response of the primary and cabin suspension has been compared with the response of primary suspension under step excitation.